PEMANFAATAN MODEL CTL UNTUK MENINGKATKAN HASIL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MAN 1 LABUHANBATU - Jailani Syahputra Siregar; Betti Megawati; Fauzi Ahmad Syawaluddin (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
In Islam education has very important position. One of the most important elements in education is learning. This study aims to see the use of the CTL model in improving the learning outcomes of Islamic Religious Education. It is important to do research because learning Islamic Religious Education is an important lesson in human life. The type of research is descriptive research. The research was conducted at MAN 1 Labuhanbatu with a research focus on learning Islamic Religious Education. Research results if the CTL model takes place in a three-step process. The first step of the process is planning. The second process step is implementation. The third process step is evaluation. From the three steps of the process, it was successful to prove that the use of the CTL model in learning Islamic Religious Education resulted in changes in the situation and condition of the class when learning was carried out. Students are more enthusiastic in participating in learning. Students are more enthusiastic and active in responding to what is conveyed by the teacher. Communication also looks more interactive.